HUBUNGAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR KOGNITIF SISWA SMP KELAS IX MATA PELAJARAN IPA DI MASA PANDEMI COVID-19 - Aisah, Uswatun; Sartika, Septi Budi (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2022)
Changes in the learning climate due to the Covid-19 pandemic, through online learning, have also influenced student learning motivation, even affecting student learning outcomes. This study aims (1). To describe whether or not there is an effect of learning motivation on science learning outcomes in grade IX SMP Islam Terpadu Darul Fikri Sidoarjo; (2). To describe how the contribution of learning motivation to student learning outcomes in grade IX SMP Islam Terpadu Darul Fikri Sidoarjo. The approach used is quantitative-non-experimental correlational method. The population in this study were all class students of SMP Islam Terpadu Darul Fikri Sidoarjo who took part in the learning process with an online or online system. The sampling technique used was purposive sampling with the sample being class IX-C students of SMP Islam Terpadu Darul Fikri Sidoarjo. The research instrument used was a learning motivation questionnaire and documentation. The analytical method used to analyze the data obtained in this study using the Pearson Product Moment correlation analysis method. The results of this study indicate that the correlation value of rxy is 0.633 with t count greater than t table, namely 5.102> 2.002, which means that there is a relationship between learning motivation and student learning outcomes, with a contribution value of 40.03%. This shows that learning motivation is one of the determinants of student learning success which is quite decisive compared to other factors. Therefore it is suggested that students are expected not to ignore this by asking for guidance from parents and teachers, to foster learning motivation so that learning outcomes can be achieved maximally.